2019
DOI: 10.1093/pm/pnz148
|View full text |Cite
|
Sign up to set email alerts
|

Classism in Pain Care: The Role of Patient Socioeconomic Status on Nurses’ Pain Assessment and Management Practices

Abstract: Objective Research on social disparities in pain care has been mainly focused on the role of race/racism and sex/sexism. Classism in pain assessment and management practices has been much less investigated. We aimed to test the effect of patient socioeconomic status (SES; a proxy of social class) on nurses’ pain assessment and management practices and whether patient SES modulated the effects of patient distress and evidence of pathology on such practices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 38 publications
1
19
2
Order By: Relevance
“…Association between SES and pain care are well described in the literature, especially in regard to chronic pain care, with patients from lower SES neighbourhoods more likely to develop chronic pain, and be prescribed opiate medications (Booher, 2019; Gebauer et al., 2017). In experimental studies, nurses have been shown to assess patients with low SES as having less intense pain and patients reports of pain less credible (Brandão et al., 2019); however, exact causal relationships in the ED have not been documented and will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Association between SES and pain care are well described in the literature, especially in regard to chronic pain care, with patients from lower SES neighbourhoods more likely to develop chronic pain, and be prescribed opiate medications (Booher, 2019; Gebauer et al., 2017). In experimental studies, nurses have been shown to assess patients with low SES as having less intense pain and patients reports of pain less credible (Brandão et al., 2019); however, exact causal relationships in the ED have not been documented and will require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“… 71 , 378 , 379 Patients with lower SES and chronic pain have been viewed by health care providers to be less competent and compliant in the use of medications and other multidisciplinary therapies for pain. 163 , 369 They have been thought by physicians to have less self-control over medication use with a greater propensity to misuse opioids and so studies have found that physicians disproportionately require them to complete opioid contracts compared to patients with higher SES. 59 , 273 , 369 , 380 Patients with lower SES have been considered by health care providers to be more “demanding,” 163 (p2094) and their pain has been referred to in “dehumanizing” ways.…”
Section: Discussionmentioning
confidence: 99%
“… 163 , 369 They have been thought by physicians to have less self-control over medication use with a greater propensity to misuse opioids and so studies have found that physicians disproportionately require them to complete opioid contracts compared to patients with higher SES. 59 , 273 , 369 , 380 Patients with lower SES have been considered by health care providers to be more “demanding,” 163 (p2094) and their pain has been referred to in “dehumanizing” ways. 378 (p152) Tamayo-Sarver and colleagues 79 wrote that SES was associated with “physicians’ perceptions of patients’ abilities, personalities, behaviors, and role demands” and that physicians “may treat patients preferentially if there is less social distance between them.” (p1245) Green and colleagues 15 suggested that more research is needed to better understand the factors that “systematically influence” physicians’ decisions regarding pain management.…”
Section: Discussionmentioning
confidence: 99%
“…Diniz et al (2020) looked at how nurses conceptualize patients of different socioeconomic status (SES) and found that while patients with middle SES were depicted mostly with positive (autonomous and communicative), patients with low‐SES were also imagined with dehumanizing traits such as “passive towards pain, with poor future prospects and referred to psychoeducation” (Diniz et al, 2020, p. 152). Brandão et al (2019) found differences in how nurses perceived utterances of pain by patients with different SES. “The low‐SES patient's pain was assessed as less intense, more attributed to psychological factors, and considered less credible (in the presence of distress cues) than the higher‐SES patient's pain” (Brandão et al., 2019, p. 2094).…”
Section: Who Is the Person In Pccmentioning
confidence: 99%
“…Brandão et al (2019) found differences in how nurses perceived utterances of pain by patients with different SES. “The low‐SES patient's pain was assessed as less intense, more attributed to psychological factors, and considered less credible (in the presence of distress cues) than the higher‐SES patient's pain” (Brandão et al., 2019, p. 2094). Diversity dimensions interact with one another in intersectionality.…”
Section: Who Is the Person In Pccmentioning
confidence: 99%